Christiansen Feature Map From the Lunar Reconnaissance Orbiter Diviner Lunar Radiometer Experiment: Improved Corrections and Derived Mineralogy. Issue 6 (17th June 2021) - Lucey, Paul G.; Greenhagen, Benjamin; Donaldson Hanna, Kerri; Bowles, Neil; Flom, Abigail; Paige, David A.
Abstract: Maps of plagioclase, olivine, and pyroxene at 1 km resolution are derived from a combination of data from the Diviner Lunar Radiometer on the Lunar Reconnaissance Orbiter and the Kaguya Multiband Imager. The Diviner instrument features three infrared bands designed to characterize a spectral feature of lunar soils that is sensitive to the average silica polymerization of the surface called the Christiansen Feature, which is directly sensitive to the presence of plagioclase, the dominant lunar silicate. Existing global mineral maps based on near‐IR data largely infer the presence of plagioclase from the bright mineral's effect on total reflectance, excepting in rare locations where the surface is nearly pure plagioclase and a weak feature in the plagioclase near‐IR spectrum can be relied upon. By integrating both wavelength regions we produced more robust estimates of the abundance of the three dominant minerals. In the process of this work, we also improved the removal of space weathering effects from Christiansen Feature maps, and showed that silica rich compositional anomalies could be reliably detected by decorrelating Christiansen Feature and FeO maps. New silica‐rich locations are reported as are the global abundances of the three major silicates. Plain Language Summary: One of the goals of remote sensing of the Moon is to produce maps of the minerals present on its surface. In this paper, we bring together two infrared spectroscopic data sets to create maps of the minerals plagioclase, pyroxene, and olivine at a resolution of 1 km. One of these infrared data sets defines the wavelength position of a spectral phenomenon called the Christiansen Feature that is sensitive to the presence of unusual silica‐rich minerals that indicate a relatively rare but widespread style of lunar volcanism. Using these new data, we find a few previously unrecognized silica‐rich exposures that extend the spatial range of these features. The Christiansen Feature is also sensitive to rare rock types that may represent outcrops of the lunar mantle at the surface of the Moon, and a promising candidate is revealed at the farside crater Titov. Key Points: The global abundance of plagioclase, pyroxene and olivine are presented The effects of space weathering on Christiansen Feature maps are removed with an improved algorithm New silica‐rich locations are identified in the Oceanus Procellarum region